Analisis Kemampuan Menulis Huruf Hijaiyah Pada Siswa Kinestetik Madrasah Aliyah Negeri (MAN) 1 Medan - fadlan rawi naustion; Mario Bagus Sanjaya; Muhammad Hasan Basri Btr; Nur Zakiah Harahap; Sahkholid Nasution (Yayasan Haiah Nusratul Islam, 2024)
The study of Arabic language there are four basic skills that must be mastered and the four skills are often heard as maharah, in Arabic language learning has four maharah namely istima' (listening), kalam (speaking), qira'ah (reading), and kitabah (writing). The purpose of this study is to provide an overview to students and teachers about the importance of learning maharah kitabah to Arabic writing. This research uses qualitative research methods and literature review studies. Maharah kitabah is a skill that focuses a person in writing hijaiyah letters from what he thinks from simple things to become an essay or rewrite the writing they have read into a book by following the rules of Arabic writing that are appropriate and relevant. The conclusion in the research that researchers found that the knowledge of students in class X.16 kinesthetic Man 1 Medan is still very lacking regarding the rules of maharah kitabah.